THE REFORM OF SERBIAN SCHOOL SYSTEM IN THE HABSBURG MONARCHY 1769-1777 - Ненад Нинковић (Истраживања, 2011)
Results of the reforms in the seventies of the eighteenth century, which were implemented by the will of Vienna throughout the Habsburg monarchy, were that the education system went under the supervision of the state, and the school was secularized to a great extent. This was the case with the Serbian primary schools as well, which were reformed between 1769 and 1777, what made a good basis for expanding the school network and improving the instruction. Implementation of these measures was entrusted to the school principals, Teodor Janković Mirjevski, Stefan Vujanovski and Avram Mrazović, in which they had a lot of success. Unlike the rest of the Monarchy, the church supported the school reform in Serbs with its considerable influence. However, the secularization in the educational process in Serbs was implemented more decisive and deeper than in other nations.